Insilico prediction of toxicity of ligands utilizing admetsar (Funded Work) - ARCHANA MOON; DEEBA KHAN; PRANJALI GAJBHIYE; MONALI JARIYA (International Journal of Pharma and Bio Sciences, 2017)
Urinary tract infection (UTI) is a commonly occurring bacterial infection also called as bladder infection or acute cystitis. Emergence of antibiotic resistance has become a serious problem worldwide. The extensive and uncontrolled use of antibiotics increases the number of multidrug resistant (MDR) bacterial strains. As bacteria have emerged multidrug resistant (MDR), that has put all human beings with a risk of limited treatment options along with increased mortality. Hence, there is an urgent need to search for a new antibacterial agent. In the current study Absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis has been performed using AdmetSAR computationally. However, the experimental evaluation of ADMET profiles is costly, and the work load cannot meet the demands of drug screening and lead optimization. In conjunction with high throughput in vitro screening, computational techniques that can filter/predict ADMET profiles have become an alternative approach. An ADME Toxicity study shows the best possible choice of drug against DHFR & DHPS proteins of the folate pathway. The DHFR and DHPS are the enzymes essential for the growth and propagation of bacteria. It is broadly seen that the alterations /mutations in DHFR AND DHPS is one of the reason for the emergence of multidrug resistance in pathogenic bacteria. The folate metabolic pathway leads to synthesis of required precursors for cellular function and contains a critical node, dihydrofolate reductase (DHFR), which is shared between prokaryotes and eukaryotes. The DHFR enzyme is currently targeted by methotrexate in anti-cancer therapies, by trimethoprim for antibacterial uses, and by pyrimethamine for anti-protozoal applications. An additional anti-folate target is dihyropteroate synthase (DHPS), which is unique to prokaryotes as they cannot acquire folate through dietary means. It has been demonstrated as a primary target for the longest standing antibiotic class, the sulfonamides, which act synergistically with DHFR inhibitors.21So, these drugs after appropriate in vivo and in vitro assays can be taken up for formulation development and further for clinical studies as an investigational drug for treatment of MDR-UTI.